Social media Influencers’ credibility on Green Purchase Behavior: Evidence from Bangladesh - Shahabuddin, A.M. (CV. Inara, 2024)
The rising global awareness of environmental issues and health consciousness after COVID 19 have driven consumers to seek more sustainable lifestyles, significantly propelled green purchasing intent into the limelight. In regions where environmental education might be lacking, influencers can fill this gap. Social media Influencers often provide educational content on the importance of sustainability and how consumers can make greener choices, which can lead to more informed purchasing decisions. The purpose of the study is to ascertain the credibility of social media influencers' mastery on purchase intentions of individuals and how these intentions are carried over into actual green purchase behaviors. A quantitative, conveynience sampling uses an online survey that conducted from November 2023 to January 2024 on a south Asian country, Bangladesh. Data were coded in SPSS 26 and regressions, the sobel test were performed to find out mediating relationship. The results shows eco labeling had mediated the relationship on social media and green purchase intentions, while social media influencers’ trust worthiness has impact on purchase. These findings have important implications for marketers and policymakers aiming to promote sustainable consumption.